Abnormalities of Skeletal Muscle, Adipocyte Tissue, and Lipid Metabolism in Heart Failure: Practical Therapeutic Targets - Takada, Shingo; Sabe, Hisataka; Kinugawa, Shintaro (Frontiers in Cardiovascular Medicine, 2020)
Chronic diseases, including heart failure (HF), are often accompanied with skeletal muscle abnormalities in both quality and quantity, which are the major cause of impairment of the activities of daily living and quality of life. We have shown that skeletal muscle abnormalities are a hallmark of HF, in which metabolic pathways involving phosphocreatine and fatty acids are largely affected. Not only in HF, but the dysfunction of fatty acid metabolism may also occur in many chronic diseases, such as arteriosclerosis, as well as through insufficient physical exercise. Decreased fatty acid catabolism affects adenosine triphosphate (ATP) production in mitochondria, via decreased activity of the tricarboxylic acid cycle; and may cause abnormal accumulation of adipose tissue accompanied with hyperoxidation and ectopic lipid deposition. Such impairments of lipid metabolism are in turn detrimental to skeletal muscle, which is hence a chicken-and-egg problem between skeletal muscle and HF. In this review, we first discuss skeletal muscle abnormalities in HF, including sarcopenia; particularly their association with lipid metabolism and adipose tissue. On the other hand, the precise mechanisms involved in metabolic reprogramming and dysfunction are beginning to be understood, and an imbalance of daily nutritional intake of individuals has been found to be a causative factor for the development and worsening of HF. Physical exercise has long been known to be beneficial for the prevention and even treatment of HF. Again, the molecular mechanisms by which exercise promotes skeletal muscle as well as cardiac muscle functions are being clarified by recent studies. We propose that it is now the time to develop more “natural” methods to prevent and treat HF, rather than merely relying on drugs and medical interventions. Further analysis of the basic design of and molecular mechanisms involved in the human body, particularly the inextricable association between physical exercise and the integrity and functional plasticity of skeletal and cardiac muscles is required.